DNA Methylation Signature in Monozygotic Twins Discordant for Psoriatic Disease - Vecellio, Matteo; Paraboschi, Elvezia Maria; Ceribelli, Angela; Isailovic, Natasa; Motta, Francesca; Cardamone, Giulia; Robusto, Michela; Asselta, Rosanna; Brescianini, Sonia; Sacrini, Francesco; Costanzo, Antonio; De Santis, Maria; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Psoriatic disease is a multifactorial inflammatory condition spanning from skin and nail psoriasis (Pso) to spine and joint involvement characterising psoriatic arthritis (PsA). Monozygotic twins provide a model to investigate genetic, early life environmental exposure and stochastic influences to complex diseases, mainly mediated by epigenetics. Methods: We performed a genome-wide DNA methylation study on whole blood of monozygotic twins from 7 pairs discordant for Pso/PsA using the Infinium Methylation EPIC array (Illumina). MeDiP – qPCR was used to confirm specific signals. Data were replicated in an independent cohort of 7 patients with Pso/PsA and 3 healthy controls. Transcriptomic profiling was performed by RNAseq on the same 7 monozygotic twin pairs. Results: We identified 2,564 differentially methylated positions between psoriatic disease and controls, corresponding to 1,703 genes, 59% within gene bodies. There were 19 regions with at least two DMPs within 1 kb of distance and significant within-pair Δβ-values (p<0.005), among them SNX25, BRG1 and SMAD3 genes, all involved in TGF-β signaling pathway, were identified. Co-expression analyses on transcriptome data identified IL-6/JAK/STAT3 and TNF-a pathways as important signaling axes involved in the disease, and they also suggested an altered glucose metabolism in patients’ immune cells, characteristic of pro-inflammatory T lymphocytes. Conclusions: The study suggests the presence of an epigenetic signature in affected individuals, pointing to genes involved in immunological and inflammatory responses. This result is also supported by transcriptome data, that altogether suggest a higher activation state of the immune system, that could promote the disease status.